Paz y guerra, represión y libertad: autonomía urbana y expansión principesca en el Sacro Imperio Romano Germánico medieval (Edad Media. Revista de Historia, 2018)
The medieval Holy Roman Empire saw complex interactions of towns and their noble partners and enemies. On a regional level, working together in leagues of peace (Landfriedensbünde), urban and noble members co-operated and struggled for the preservation of peace and against the general insecurity. But, at the same time, striving to restrict urban autonomy, powerful princes successfully led an expansionist policy and consolidated their territories. Chronicles, documents from assemblies, letters and literary works show that in their relations with nobility, towns were forced to keep a dangerous balance of co-operation and confrontation. Sometimes they had to pay a high price and even had to take part in the repression of revolts.